A method for preparing ultrafine narrow particle size high density copper powder

By regulating the ratio and pH of copper salt and complexing agent, combined with an appropriate amount of dispersant, ultrafine narrow particle size high-density copper powder is prepared by sedimentation method, which solves the problems caused by the addition of polymer dispersants in the prior art and achieves high efficiency. Low-cost copper powder preparation.

CN118513560BActive Publication Date: 2025-02-18XIAMEN ZIJIN NEW ENERGY & NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410641095.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-02-18
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

In the existing ultrafine copper powder preparation method, adding a large amount of polymer dispersant will reduce the bonding force and thermal stability of the copper powder, affect the mechanical properties and high temperature resistance of the product, and increase the difficulty and cost of the washing process.

Method used

By adjusting the complexing ratio of copper salt and complexing agent and solution pH, combined with an appropriate amount of dispersant addition, the solid-liquid separation of copper powder is achieved by using the sedimentation method, and the washing and filtration process is simplified.

Benefits of technology

The stable preparation of spherical copper powder of different particle sizes is achieved, which improves the dispersion and density of copper powder, and reduces the preparation cost and the economic cost of the washing and filtration process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118513560B_ABST
    Figure CN118513560B_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing ultrafine, narrow-particle-size, high-density copper powder. This method can stably prepare narrow-particle-size, near-spherical copper powders with different particle sizes (D50 = 0.3-8 μm) simply by adjusting the complexation ratio and solution pH. Furthermore, in this method, no additional dispersant is needed when preparing copper powder with D50 ≥ 1.1 μm, and only a small amount of dispersant is required when preparing copper powder with D50 < 1.1 μm. This allows for solid-liquid separation of copper powder within the acceptable particle size range via sedimentation, greatly simplifying subsequent washing and filtration processes and reducing the time, economic costs, and subsequent wastewater treatment costs. Moreover, this method is inexpensive, requires simple equipment, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nonferrous metal materials, and in particular to a method for preparing ultrafine, narrow-grained, high-density copper powder. Background Art

[0002] Ultrafine copper powder has the characteristics of high purity, high conductivity and high specific surface area. In the field of electronics industry, it is mainly used for the preparation of conductive materials, such as conductive coatings, conductive adhesives, conductive films, etc. It can form a conductive layer on the surface of electronic devices, providing excellent conductive properties and signal transmission efficiency; in shielding materials, it can effectively absorb and shield electromagnetic radiation signals through its high conductivity and high specific surface area, providing better shielding effect; in the field of catalysis, due to the characteristics of high purity and large specific surface area, ultrafine copper powder can be used as a carrier or active component of catalysts to participate in various catalytic reactions, such as the application of catalysts in organic synthesis and water treatment.

[0003] The most commonly used method for preparing ultrafine copper powder is the liquid phase method. In the liquid phase reduction preparation process, a large amount of polymer dispersant is often needed to ensure the dispersibility and stability of the ultrafine copper powder. However, this method of adding polymer dispersants also has some disadvantages: adding a large amount of polymer dispersants will change the molecular structure attached to the surface of the copper powder, reduce the bonding force and thermal stability of the copper powder, make it difficult to form a dense compact, and affect the mechanical properties and high temperature resistance of the product; the molecules of the polymer dispersant will wrap on the surface of the copper powder to form a surface layer that is difficult to remove, significantly reducing the conductivity of the copper powder, and will be affected in some fields that require high conductivity, such as electromagnetic shielding, conductive coatings, etc.; in the preparation process of ultrafine copper powder, a large amount of dispersant will also increase the viscosity of the reaction solution, which brings great difficulties to the subsequent washing process. At the same time, the added polymer dispersant may remain in the product and affect the subsequent processing, application, etc., potentially affecting the stability and reliability of the product. Therefore, developing a process for preparing ultrafine copper powder with a simple and environmentally friendly preparation process, precise particle size control, and a small amount of polymer dispersant added has significant market and economic value. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention aims to provide a method for preparing ultrafine, narrow-particle, high-density copper powder.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A method for preparing ultrafine, narrow-grained, high-density copper powder comprises the following steps:

[0007] S1. Mix the copper salt and the complexing agent in a set ratio to form a target complex state, and then heat to 55-65°C;

[0008] S2. Adjust the pH, raise the temperature to 75-85°C, and then add a reducing agent to carry out a reduction reaction according to the particle size requirement of the copper powder. When the particle size requirement of the copper powder is D50 ≥ 1.1 μm, no dispersant is needed. When the particle size requirement of the copper powder is D50 < 1.1 μm, a dispersant is added.

[0009] S3, pumping the reaction product obtained in step S2 into a sedimentation tank for primary sedimentation, and then performing the following treatment according to the particle size requirements of the copper powder:

[0010] When the particle size requirement of the copper powder is D50≥1.1μm, pour out the supernatant and add pure water to the remaining material for secondary sedimentation. After the sedimentation is completed, pour out the supernatant, and filter and dry the remaining material to obtain a copper powder with narrow particle size, high density and good dispersibility.

[0011] When the particle size requirement of the copper powder is D50<1.1μm, a ceramic filtration system is used for concentration and washing after the first sedimentation, and a copper powder with narrow particle size, high density and good dispersibility is obtained after filtration and drying.

[0012] Furthermore, in step S1, the copper salt includes one or more of copper chloride, copper sulfate, copper acetate, copper nitrate, and cuprous chloride, the complexing agent is concentrated ammonia water, and the molar ratio of the copper salt to the ammonia water is 1:0.3-3.5.

[0013] Furthermore, in step S2, ascorbic acid and NaOH solution are added to adjust the pH. During the pH adjustment, the molar ratio of copper salt to ascorbic acid is 1:0-0.05, the concentration of ascorbic acid is 1-3 mol / L, the molar ratio of copper salt to NaOH is 1:0.3-2.1, and the concentration of NaOH solution is 1.5-4 mol / L.

[0014] Furthermore, in step S2, the reducing agent is ascorbic acid, the molar ratio of copper salt to ascorbic acid is 1:1-1.4, and the concentration of ascorbic acid is 1-3 mol / L.

[0015] Furthermore, in step S2, the dispersant includes one or more of gelatin, PVP, EDTA-2Na, and gum arabic, and the mass ratio of the dispersant to the copper salt is 0-25%wt.

[0016] Furthermore, in step S2, the reaction time is 30-60 min.

[0017] Furthermore, in step S3, the drying condition is forced air drying at 60-80° C. for 3-24 hours.

[0018] Furthermore, in step S3, the first sedimentation time is 5-20 min, and the second sedimentation time is 20-60 min.

[0019] The beneficial effects of the present invention are as follows: in the method of the present invention, narrow-particle-size spherical copper powders of different particle sizes such as D50=0.3-8 μm can be stably prepared only by adjusting the complexing ratio of copper salt and complexing agent and the pH of the solution, and in the method of the present invention, no additional dispersant is required in the process of preparing copper powder with D50≥1.1 μm, and only a small amount of dispersant is required in the preparation of copper powder with D50<1.1 μm, so that the solid-liquid separation of copper powder can be achieved by sedimentation method within the particle size that can be prepared, which greatly simplifies the subsequent washing and filtering process, reduces the time, economic cost and subsequent sewage treatment cost of the washing and filtering process. In addition, the method of the present invention has low preparation cost, simple equipment, and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a flow chart of the preparation method of each embodiment of the present invention;

[0021] Figure 2 This is a scanning electron microscope image of the copper powder prepared in Example 1 of the present invention;

[0022] Figure 3 This is a scanning electron microscope image of the copper powder prepared in Example 2 of the present invention;

[0023] Figure 4 This is a scanning electron microscope image of the copper powder prepared in Example 3 of the present invention;

[0024] Figure 5 This is a scanning electron microscope image of the copper powder prepared in Example 4 of the present invention.

[0025] Figure 6 This is a scanning electron microscope image of the copper powder prepared in Example 5 of the present invention.

[0026] Figure 7 This is a scanning electron microscope image of the copper powder prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with the accompanying drawings. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and specific operation process, but the protection of the present invention is not limited to this embodiment.

[0028] Example 1

[0029] This embodiment provides a method for preparing ultrafine, narrow-grained, high-density copper powder. Figure 1 As shown, the specific process is:

[0030] (1) Take 1000 mL of 1.5 mol / L copper sulfate solution, stir it thoroughly at room temperature, add 395 mL of concentrated ammonia water (the molar ratio of copper sulfate to ammonia water is 1:3.5), stir for 10 min, and then heat the resulting solution to 55°C.

[0031] (2) Add 50 mL of 1.5 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:0.05) and 770 mL of 4 mol / L NaOH (the molar ratio of copper sulfate to NaOH is 1:2.1) to adjust the pH, and then heat the resulting solution to 75°C;

[0032] (3) Add 1000 mL of 2.1 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:1.4) and 56 g of PVP-K23 (the mass ratio to copper sulfate is 23.3%) and react for 60 min.

[0033] (4) After the reaction is completed, the mixture is pumped into a sedimentation tank and allowed to settle for 20 minutes.

[0034] (5) Pump into the ceramic filtration system for washing and concentration.

[0035] (6) After filtration, the powder product was dried under 60°C for 3 h. It was spherical and had good dispersibility. Its D50 was 0.53 μm, D90 was 0.77 μm, and the tap density was 3.63 g / cm 3 , SEM images are shown in Figure 2 shown.

[0036] Example 2

[0037] This embodiment provides a method for preparing ultrafine, narrow-grained, high-density copper powder. Figure 1 As shown, the specific process is:

[0038] (1) Take 1000 mL of 2 mol / L copper sulfate solution, stir it thoroughly at 40°C, add 400 mL of 25% concentrated ammonia water so that the molar ratio of copper sulfate to ammonia water is 1:2.68, stir for 10 min, and then heat the resulting solution to 65°C;

[0039] (2) Add 20 mL of 2 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:0.02) and 850 mL of 3 mol / L NaOH (the molar ratio of copper sulfate to sodium hydroxide is 1:1.28) to adjust the pH, and heat the resulting solution to 85°C;

[0040] (3) Add 1080 mL of 2 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:1.08) and 50 g of PVP-K23 (the mass ratio to copper sulfate is 15.6%) and react for 30 min.

[0041] (4) After the reaction is completed, the material obtained in step (3) is pumped into a sedimentation tank and allowed to settle for 20 minutes.

[0042] (5) Pump into the ceramic filtration system for washing and concentration.

[0043] (6) After filtration, the powder product was dried under 60°C for 6 h. It was spherical and had good dispersibility. Its D50 was 0.34 μm, D90 was 0.51 μm, and the tap density was 3.12 g / cm 3 , SEM images are shown in Figure 3 shown.

[0044] Example 3

[0045] This embodiment provides a method for preparing ultrafine, narrow-grained, high-density copper powder. Figure 1 As shown, the specific process is:

[0046] (1) Take 1000 mL of 2 mol / L copper sulfate solution, stir it thoroughly at 40°C, add 360 mL of concentrated ammonia water (the molar ratio of copper sulfate to ammonia water is 1:2.4), stir for 10 min, and then heat the resulting solution to 65°C;

[0047] (2) 30 mL of 2 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:0.03) and 685 mL of 3.5 mol / L NaOH (the molar ratio of copper sulfate to NaOH is 1:1.2) were added to adjust the pH, and then the resulting solution was heated to 85°C;

[0048] (3) Add 980 mL of 2 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:0.98) and 15 g of PVP-K23 (the mass ratio to copper sulfate is 4.7%) and react for 30 min.

[0049] (4) After the reaction is completed, the mixture is pumped into a sedimentation tank and allowed to settle for 20 minutes;

[0050] (5) Pump into the ceramic filtration system for washing and concentration.

[0051] (6) After filtration, the powder product was dried under 60°C for 6 h. The powder product was spherical and had good dispersibility. Its D50 was 0.69 μm, D90 was 0.83 μm, and the tap density was 3.71 g / cm 3 , SEM images are shown in Figure 4 shown.

[0052] Example 4

[0053] This embodiment provides a method for preparing ultrafine, narrow-grained, high-density copper powder. Figure 1As shown, the specific process is:

[0054] (1) Take 1000 mL of 1.5 mol / L copper sulfate solution, stir it thoroughly at room temperature, add 240 mL of concentrated ammonia water (the molar ratio of copper sulfate to ammonia water is 1:2.14), stir for 5 min, and then heat the resulting solution to 60°C.

[0055] (2) Add 10 mL of 1.5 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:0.01) and 335 mL of 2.5 mol / L NaOH (the molar ratio of copper sulfate to NaOH is 1:0.56) to adjust the pH, and then heat the resulting solution to 80°C;

[0056] (3) Add 1050 mL of 1.5 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:1.05) and react for 50 min.

[0057] (4) After the reaction is completed, the mixture is pumped into a sedimentation tank and allowed to settle for 10 minutes.

[0058] (5) Pour out the supernatant and add pure water for secondary sedimentation for 30 min.

[0059] (6) After filtration, the powder product was dried under 60°C for 3 h. It was spherical and had good dispersibility. Its D50 was 1.21 μm, D90 was 1.47 μm, and the tap density was 4.16 g / cm 3 , SEM images are shown in Figure 5 shown.

[0060] Example 5

[0061] This embodiment provides a method for preparing ultrafine, narrow-grained, high-density copper powder. Figure 1 As shown, the specific process is:

[0062] (1) Take 1000 mL of 1.5 mol / L copper sulfate solution, stir it thoroughly at room temperature, add 150 mL of concentrated ammonia water (the molar ratio of copper sulfate to ammonia water is 1:1.34), stir for 5 min, and heat the resulting solution to 60°C;

[0063] (2) Add 5 mL of 1.5 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:0.005) and 240 mL of 3 mol / L NaOH (the molar ratio of copper sulfate to NaOH is 1:0.48), and heat the resulting solution to 75°C.

[0064] (3) Add 1000 mL of 1.5 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:1) and react for 60 min.

[0065] (4) After the reaction is completed, the mixture is pumped into a sedimentation tank and allowed to settle for 5 minutes.

[0066] (5) Pour out the supernatant and add pure water for secondary sedimentation for 20 min.

[0067] (6) After filtration, the powder product was dried under 60°C for 3 h. It was spherical and had good dispersibility. Its D50 was 3.26 μm, D90 was 4.73 μm, and the tap density was 5.62 g / cm 3 , SEM images are shown in Figure 6 shown.

[0068] Example 6

[0069] This embodiment provides a method for preparing ultrafine, narrow-grained, high-density copper powder. Figure 1 As shown, the specific process is:

[0070] (1) Take 1000 mL of 1.5 mol / L copper sulfate solution, stir it thoroughly at room temperature, add 34 mL of concentrated ammonia water (the molar ratio of copper sulfate to ammonia water is 1:0.3), stir for 5 min, and then heat the resulting solution to 60°C.

[0071] (2) 300 mL of 1.5 mol / L NaOH (the molar ratio of copper sulfate to NaOH is 1:0.3) was added to adjust the pH, and the resulting solution was heated to 75°C.

[0072] (3) Add 1000 mL of 1.5 mol / L ascorbic acid (the molar ratio of copper sulfate to ascorbic acid is 1:1) and react for 60 min.

[0073] (4) After the reaction is completed, the mixture is pumped into a sedimentation tank and allowed to settle for 5 minutes.

[0074] (5) Pour out the supernatant and add pure water for secondary sedimentation for 20 min.

[0075] (6) After filtration, the powder product was dried under 60°C for 3 h. It was spherical and had good dispersibility. Its D50 was 7.91 μm, D90 was 14.15 μm, and the tap density was 5.13 g / cm 3 , SEM images are shown in Figure 7 shown.

[0076] For those skilled in the art, various corresponding changes and modifications can be made according to the above technical solutions and concepts, and all of these changes and modifications should be included in the protection of the claims of the present invention.

Claims

1. A method for preparing ultrafine, narrow-particle, high-density copper powder, characterized in that: The steps include: S1. Mix the copper salt and the complexing agent in a set ratio to form a target complex state, and then heat to 55-65° C.; the copper salt includes one or more of copper chloride, copper sulfate, copper acetate, copper nitrate, and cuprous chloride; the complexing agent is concentrated ammonia water, and the molar ratio of the copper salt to the ammonia water is 1:0.3-3.5; S2, adjusting the pH, raising the temperature to 75-85°C, and then adding a reducing agent to react according to the particle size requirement of the copper powder, and when the particle size requirement of the copper powder is D50 ≥ 1.1 μm, no dispersant is needed, and when the particle size requirement of the copper powder is D50 < 1.1 μm, a dispersant is added; adding ascorbic acid and NaOH solution to adjust the pH, in which the molar ratio of copper salt to ascorbic acid is 1:0-0.05, the concentration of ascorbic acid is 1-3 mol / L, the molar ratio of copper salt to NaOH is 1:0.3-2.1, and the concentration of NaOH solution is 1.5-4 mol / L; S3, pumping the reaction product obtained in step S2 into a sedimentation tank for primary sedimentation, and then performing the following treatment according to the particle size requirements of the copper powder: When the particle size requirement of the copper powder is D50≥1.1μm, pour out the supernatant and add pure water to the remaining material for secondary sedimentation. After the sedimentation is completed, pour out the supernatant, and filter and dry the remaining material to obtain a copper powder with narrow particle size, high density and good dispersibility. When the particle size requirement of the copper powder is D50<1.1μm, a ceramic filtration system is used for concentration and washing after the first sedimentation, and a copper powder with narrow particle size, high density and good dispersibility is obtained after filtration and drying.

2. The method according to claim 1, characterized in that In step S2, the reducing agent is ascorbic acid, the molar ratio of copper salt to ascorbic acid is 1:1-1.4, and the concentration of ascorbic acid is 1-3 mol / L.

3. The method according to claim 1, characterized in that: In step S2, the dispersant includes one or more of gelatin, PVP, EDTA-2Na, and gum arabic, and the mass ratio of the dispersant to the copper salt is 0-25%wt.

4. The method according to claim 1, characterized in that: In step S2, the reaction time is 30-60 min.

5. The method according to claim 1, characterized in that In step S3, the drying condition is forced air drying at 60-80°C for 3-24 hours.

6. The method according to claim 1, characterized in that In step S3, the first sedimentation time is 5-20 min, and the second sedimentation time is 20-60 min.

Citation Information

Patent Citations

  • Method for preparing antioxidated superfine copper powder

    CN101474678A

  • Process for producing copper powder and copper powder

    CN101801568A